PENGGUNAAN METODE ACTIVE LEARNING TIPE POWER OF TWO TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS SMA NEGERI 3 PADANG - Santri, Mely - (Pendidikan Sosiologi, 2014)
This research is motivated by the results of student learning in subjects low in sociologyclass XI IPS SMAN 3 Padang. This study aims to determine partnered with using active methodsof learning the type of power of two sociologi student learning outcomes can be improved in classXI IPS SMAN 3 Padang. This tipe of research is the study experimental. The population in thisstudy were all students of class XI IPS SMAN 3 Padang comprising of two class. The samplingtechnique was done by purposive sampling, class XI IPS 2 as the experimental class and the classXI IPS 1 as the control class. The instrument used in this study is the final test. The form of thetest used is multiple choice with reliability test is r 11 = 0,841. Based on the analysis of dataobtained final test average student learning outcomes experimental class was 86,62 higher than thecontrol class is 76,32. Data analysis was performed obtained t = 4,522 is greater than t table =1,67. This it can be concluded that the results of studying sociologi students using active learningmethods of two types of power can be increasedtn in class XI IPS SMAN 3 Padang, because byusing the method of active learning is the type of power of two vibrant and active student learningso that student learning outcomes increase.